The land left behind: a systematic review of transnational migration-induced change and its implication for rural sustainability in Nepal - Saroj Koirala; Soniya Bashyal (Humanities & Social Sciences Communications)
Abstract This article provides a comprehensive analysis of the multifaceted impacts of transnational migration in Nepal, drawing on findings from 42 systematically selected research articles. Employing a thematic analysis approach, the study constructs a schematic representation delineating four key themes: the use effect of remittance income on individuals, the offset effect on land, the substitution effect on people due to a reduced workforce, and the neglect effect on land stemming from decreased working members in households and communities. This comprehensive examination sheds light on the migration dynamics and addresses its implications for rural sustainability. The central theme underscores the connections between transnational migration and its implication for food security, livelihood enhancement, income diversification, and ecological restoration. The paper emphasizes the importance of understanding these interlinkages for informed policy decisions aligned with long-term macroeconomic goals. The synthesized framework contributes to theoretical foundations and encourages further research on the impacts of transnational migration in agrarian economies and the pathways for socio-economic transitions.